Buffer based Analysis of Congestion Control in Delay Tolerant Network - Amardeep; Gahlot, Devendar; Bindra, H S (International Journal of Computer Sciences and Engineering, 2025)
In this fast changing era, information or data sharing is one of the key requirement of human and machines. Networks are designed so as to provide this facility of data sharing to the humans or machines. The networks which work under the adverse circumstances (i.e. intermittent connectivity) are termed as Delay Tolerant Networks. In the Delay Tolerant Networks, Congestion is the key area which needs to be addressed by the researcher and the community. In this paper we have proposed a novel technique for buffer management to avoid / remove the congestion in Delay Tolerant Networks. This approach for buffer management contemplates the size of message and the rest of the TTL of message for buffer management and for convenience of new approaching message at every node. Through the simulative results obtained in this study we found that the approach proposed and evaluated in this work is providing better delivery probability of the messages.